Theater within the Graphic Novel about Theater: Neil Gaiman’s Concept of the Artist in His “A Midsummer Night’s Dream” - Limpár, Ildikó (Hungarian Journal of English and American Studies, 2020)
In his own version of A Midsummer Night’s Dream, Neil Gaiman exploits the possibilities in doubling: he presents the Shakespearean comedy as a play within the artistic space of his graphic novel and Such a reading reveals that what is a tool in Shakespeare’s play to visualize that art is capable of mirroring reality becomes a means to express the interchangeability of the realistic and the fantastic realms. Gaiman’s strategy of doubling thus suggests an understanding of life that surpasses the narrow interpretation of historical facts, and thereby it may offer a viable alternative to what we experience as reality.